Nicotine reduces established L-dopa-induced dyskinesias in a monkey model of Parkinson’s disease - Quik, Maryka (2013)
BACKGROUND: Although 3,4-dihydroxyphenylalanine (L-dopa) is the gold-standard treatment for Parkinson’s disease, it can lead to disabling dyskinesias. Previous work showed that nicotine reduces L-dopa-induced dyskinesias (LIDs) in several parkinsonian animal models. The goal of this study was to determine if the time of nicotine administration affected its ability to reduce LIDs in L-dopa-primed and L-dopa naïve monkeys, and also to test if tolerance developed to nicotine’s beneficial effects. METHODS: Monkeys were injected with MPTP (1.9–2.0 mg/kg sc) over 3–5 months until parkinsonian. Nicotine (300 μg/ml) was administered in drinking water (4–6 months) to L-dopa-primed or L-dopa-naïve monkeys, with L-dopa/carbidopa (10/2.5 mg/kg) gavaged twice daily. RESULTS: One set of MPTP-lesioned monkeys (n=23) was first gavaged with L-dopa and subsequently given nicotine 4 wk later when dyskinesias have plateaud or 8 wk later when dyskinesias are established. A 60–70% decrease in LIDs was observed after several weeks of nicotine treatment in both groups. A second set of monkeys (n=26) was given nicotine 8 or 2 weeks before L-dopa. In the 8 week nicotine pretreatment group, there was an immediate reduction in LIDs, which plateaud at 60–70%. In the 2 week nicotine pretreatment group, there were initial small decreases in LIDs, which plateaud at 60–70% several weeks later. Thus, nicotine pre- and post-treatment was similarly efficacious in reducing LIDs. The beneficial effect of nicotine persisted throughout the study (17–23 weeks). Nicotine did not worsen parkinsonism. CONCLUSION: These data suggest that nicotine treatment has potential as a successful antidyskinetic therapy for Parkinson’s disease patients.